Minat Beli Konsumen terhadap Produk Minuman Bubble Tea-Xi Bo Ba Jimbaran-Bali - Wayan Indah Silvia Permatasari; I Gusti Ayu Dewi Hendriyani; Putu Mira Astuti Pranadewi (JURNAL GASTRONOMI INDONESIA, 2020)
The purpose of this study was to determine consumers 'buying interest in Xi Bo Ba's beverage products, and consumers' responses to these products. This study used a qualitative descriptive analysis technique by collecting data using an online questionnaire on 60 respondents Xi Bo Ba Jimbaran Bali. Purchase interest variable consists of 3 dimensions, namely product quality, price, promotion with a total of 5 indicators. The results of the study of 60 respondents were the highest in women, mostly students aged 17-25 years. Respondents prefer shopping online rather than offline. The conclusion of all indicators of buying interest is in the very good category, with the highest indicator on product quality and the lowest on price. The advice for company management is to maintain what is good, improve what is still lacking, including new innovations in Xi Bo Ba's products in the future.